Relationship between serum nitric oxide of patients with thyroid disorders and metabolic syndrome indices and nitrate concentration of water - Shaghayegh Jafari; Mansooreh Dehghani; Haleh Ghaem; Mahmood Soveid; Hasan Hashemi (Scientific Reports, 2023)
Abstract This case–control study aimed to assess the effect of drinking water nitrate on serum nitric oxide concentration and the risk of metabolic syndrome (MetS) in the population in the Middle East. The study included 50 control and 50 thyroid disorder cases who were referred to two medical centers in 2021. In this study, serum nitric oxide concentration, drinking water nitrate, and metabolic syndrome components were measured in the two groups. The results showed there was a statistically significant difference between serum NO in the case and control groups (p-value < 0.001). There was a positive correlation between the concentration of nitrate in drinking water and serum nitric oxide in the case and control groups; however, this relationship was not significant statistically. A statistically significant difference was found between serum nitric oxide and systolic blood pressure in the cases (p-value < 0.05), but there was no significant difference between MetS and nitric oxide. Therefore, we concluded that the relationship between nitric oxide and nitrate in consuming water should be determined in thyroid patients. In addition to their water consumption, it is better to study the nitrate of foods, especially vegetables.